EXPLORING AI TRANSLATION IN FOREIGN LANGUAGE LEARNING: ADVANTAGES, CHALLENGES AND PEDAGOGICAL INSIGHTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The rapid advancement of AI translation technologies has significantly transformed foreign language learning, offering instant translations, adaptive exercises, and personalized feedback. These tools enhance comprehension, vocabulary retention, and learner engagement. However, over-reliance on AI may hinder cognitive effort, reduce motivation, and limit oral and written language practice. Scholars such as Stephen Krashen, Merrill Swain, and Carol Chapelle emphasize that AI should complement rather than replace traditional learning methods. Proper integration fosters interactive learning, cultural awareness, and critical thinking. Ultimately, the effectiveness of AI in language acquisition depends on balanced usage, combining technological support with proven pedagogical strategies to preserve motivation and meaningful learning. this article discusses the role of AI translation in language learning and its impact on learners' motivation, comprehension and pedagogical practices